Preparation and Characterization of Whole Stem Kenaf Fibre-Poly (Butylene Adipate Co-Terephthalate) Composites - Hadithon, Kamarul Ariffin (2011)
This study focused on the preparation and characterization of whole stem kenaf (WSK) fibre with poly(butylene adipate co-terephthalate) (PBAT) by melt blending technique. The biodegradable composite were prepared at 10, 20, 30, 40 and 50% weight of fibre loading using internal mixer. The blending process was carried out for 10 minutes at 130oC with rotor speed 30 rpm. The effects of fibre loading and NaOH fibre chemical treatment on physical and thermal properties were investigated by using FT-IR, DMA, TGA, and SEM. Mechanical testing on tensile, flexural and impact were also performed. Water absorption and biodegradation tests were also studied to study the effect of fibre loading and fibre chemical treatment on biodegradability of WSK/PBAT composites. For the untreated fibre, the results show that tensile strength remained constant as filler loading from 10% to 30%, but increased at 40%. The properties of composites on flexural and impact strength were decreased with the increasing of the fibre loading. Meanwhile, the increases of tensile and flexural modulus on the composite were observed. The used of NaOH chemical treatment fibre as filler improved the mechanical properties of the composite. The NaOH treatment at 4% concentration gave the best improvement on the mechanical properties of the composite. The FT-IR spectrum of the treated fibre showed that alkaline treatment removes hemicelluloses and lignin from WSK kenaf fibre surface. The FT-IR spectrum of the blends indicated that no chemical interaction between component of the composite. Thermogravimetric analysis (TGA) confirmed the removal of hemicelluloses and lignin from WSK fibre after treatment. The DMA indicates that the storage modulus of the composites increase with the increased of the fibre loading but decreased after 40% fibre loading. The WSK fibre treatment improves the stiffness of the composite with the increase of storage modulus compared with untreated fibre composites which resulting the better interaction of fibre with matrix.